Recipes for science an introduction to scientific methods and reasoning - Potochnik, Angela; Colombo, Matteo; Wright, Cory 1975- (Routledge, 2024)
Today, scientific literacy is an essential aspect of any undergraduate education. Recipes for Science responds to this need by providing an accessible introduction to the nature of science and scientific methods, reasoning, and concepts. Key Updates to the Second Edition
Bibliographie S. [352]-360
Keywords: Wissenschaftliches Arbeiten; Methode; Wissenschaft; Science / Methodology; Science; Science / Philosophy; Science / Méthodologie